Corporate Social Responsibility: Kepemilikan Saham Manajerial Dan Kepemilikan Saham - Noor Rokhman, M. Taufiq (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Implementation of CSR activities can not be separated from theimplementation of good corporate governance. General Guidelines ofGood Corporate Governance Indonesia states that the purpose ofcorporate governance is to promote the emergence of awareness andcorporate responsibility to the community and the surroundingenvironment. One of the factors influencing the implementation ofcorporate governance CSR is the structure of managerial andinstitutional ownership. The objective of the research is to know anddescribe managerial and institutional share ownership in influencingcorporate social responsibility disclosure. The results of the researchexplain managerial share ownership and institutional share ownershipsimultaneously affect corporate social responsibility. While partiallyManagerial share ownership and institutional share ownership influenceto corporate social responsibility.Keywords: Managerial share ownership, institutional share ownership,corporate social responsibility.